The Optimum Monetary Aggregate for Stabilization Policy - Roper, Don E.; Turnovsky, Stephen J. (Quarterly Journal of Economics, 1980)
This paper presents a procedure for determining the optimal monetary aggregate for stabilization policy. To illustrate the procedure, a simple stochastic IS-LM model is used, and how, in general, stabilizing an aggregate consisting of both money and interest bearing government debt will provide superior stabilization for output is shown. The relative weight given to the two components in the aggregate may vary widely, depending upon the source of random disturbances in the economy. Also, for a specific weight, stabilizing the aggregate is equivalent to stabilizing the interest rate. Finally, we show how stabilizing the aggregate is equivalent to other forms of optimal monetary policy proposed by Poole, and Kareken, Muench, and Wallace.